The quest for Maslow’s self-actualisation need in leadership: a review of happiness in the Nigerian economy - Ewugi, Musa Salihu; Abd Karim, Mohd Zaini; Abdul Hakim, Roslan (MCSER Publishing, Rome-Italy, 2015)
The phrase “making it” or “made it” is a common phenomenon that posits ones money-making status or the wealth one has acquired in Nigerian society. The word is mainly used to describe or applaud people that have amassed wealth in the government leadership roles or used by leadership cohorts to describe their act in the business of embezzlement of public fund. Many politicians and top government officials view corruption, most especially embezzling public wealth for personal use as way of self actualisation, attaining happiness and success in Nigeria.This phenomenon has generated other societal evils that have resulted in a lot of hardship and unhappiness of Nigerian masses and even the few in the leadership positions base on Maslow’s basic needs of life. The work however, aimed at ascertaining Nigeria’s happiness status, discovered that with societal values like religion and pronounced life deprivations, the masses could be said to be happy.Therefore, concludes that justice is an icon to achieving global happiness and recommends removal of immunity provision of the constitution to curb corruption and upgrade happiness status of Nigerians.